Tight bounds for the eavesdropping collective attacks on general CV-QKD protocols that involve non-maximally entanglement - Becir, A.; Wahiddin, Mohamed Ridza (Springer, 2012)
A new method to quantify the eavesdropper’s accessible information on continuous variable quantum key distribution for protocols implementing homodyne and heterodyne detections is introduced.We have derived upper bounds for the eavesdropping collective attacks on general continuous variable quantum key distribution protocols. Our focus is especially on deriving bounds which are Gaussian optimal for Eve collective attacks that involve non maximally entanglement (i.e. Alice and Bob use non maximally entangled states or non-Gaussian modulation for their quantum key distribution protocols). The new bounds derived are tight for all continuous variable quantum key distribution protocols. We show that the eavesdropper’s accessible information is independent of the initial correlation between Alice and Bob modes in reverse reconciliation scheme, while in direct reconciliation scheme, Eve information is given as a function of Alice and Bob initial correlation.